Relación entre los esquemas desadaptativos tempranos y la ansiedad social en niños y adolescentes - Rojas Balta, Stefany Isabel (2022)
Social anxiety is considered a disorder that impairs the quality of life of people, especially children and adolescents, being considered the most common anxiety disorder in this population. Therefore, this research sought to identify the relationship between early maladaptive schemas and social anxiety in children and adolescents. A systematic search was carried out following the PRISMA guidelines (Page et al., 2021) in Web of Science, Scopus and Scielo databases. Ten research articles were analyzed that met the inclusion and exclusion criteria. The results showed three types of relationships between early maladaptive schemes and social anxiety in children and adolescents, these are: positive correlation, predictive, and mediating relationship. The predictive relationship is found in most of the studies, specifically in four of the ten selected articles.